2021
DOI: 10.17711/sm.0185-3325.2021.031
|View full text |Cite
|
Sign up to set email alerts
|

Psychological stress in mothers of neonates admitted to an intensive care unit

Abstract: Introduction. The admission of the newborn to a neonatal intensive care unit (NICU) leads to maternal stress. This stress has deleterious consequences on the mother and the appropriate attachment with her child. Objective. To assess the relationship of mothers’ sociodemographic, clinical, psychological, and psychiatric factors, as well as neonates’ clinical aspects with the level of psychological stress perceived by mothers of neonates admitted to the NICU. Method. Cross-sectional study with 47 women over the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…These include infections, hypertension, increased postpartum bleeding, generalized infections, and genital tract infections. It has been demonstrated that patients who give birth before completing 37 weeks of gestation require longer hospitalization and rehabilitation [ 70 , 71 , 72 , 73 ].…”
Section: Influence Of Prematurity On the Mother And Familymentioning
confidence: 99%
“…These include infections, hypertension, increased postpartum bleeding, generalized infections, and genital tract infections. It has been demonstrated that patients who give birth before completing 37 weeks of gestation require longer hospitalization and rehabilitation [ 70 , 71 , 72 , 73 ].…”
Section: Influence Of Prematurity On the Mother And Familymentioning
confidence: 99%